LAMA PEMAKAIAN KONTRASEPSI SUNTIK DEPO MEDROKSIPROGESTERON ASETAT DENGAN KADAR KOLESTEROL PADA AKSEPTOR KB - Ni Made Werdianti Prawerti; Nengah Runiari; I Dewa Made Ruspawan (Jurnal Gema Keperawatan, 2019)
This study aims to the relationship between duration of DMPA injection useage with cholesterole levels on family planning acceptors in South Denpasar I Primary Health Center on 2019. The type of research used is non-experimental with the type of correlational withapproach cross sectional. Sampling uses non probability sampling with a purposive sampling technique of 35 respondents. The instrument of collection through interviews and examination of cholesterol levels was measured by the Electrode-Based Biosensor method using the EasyTouch GCU Kit. The results showed that the majority of DMPA injection contraceptive use for ≥36 months (57.1%), most had rather high cholesterol levels (40.0%). The hypothesis test used is Chi-Square test with a p value = 0,000 (α = 0.05), so that there is the relationship between duration of DMPA injection useage with cholesterole levels on family planning acceptors in South Denpasar I Primary Health Center on 2019.